Changing resuscitation strategies during a pandemic: lessons from the consecutive surges in New York and global challenges. Issue 6 (27th December 2021) - Jafari, Daniel; Cohen, Allison L.; Monsieurs, Koen; Becker, Lance B.
Abstract : Purpose of review: To provide a framework for resuscitation of COVID-19 critical illness for emergency and intensive care clinicians with the most up to date evidence and recommendations in the care of COVID-19 patients in cardiac arrest or in extremis. Recent findings: Performing cardiopulmonary resuscitation (CPR) on COVID-19 patients requires the clinicians to adopt infection mitigation strategies such as full personal protective equipment, mechanical chest compression devices, and restricting the number of people present during the resuscitation. The time of intubation is a subject of ongoing research and clinicians should use their best judgment for each patient. Clinicians should prepare for CPR in prone position. Particular attention should be given to the psychological well-being of the staff. Point of care ultrasound has proved to be an invaluable diagnostic tool in assessing ventricular dysfunction and parenchymal lung disease. Although novel therapies to supplant the function of diseased lungs have shown promise in select patients the evidence is still being collected. The end-of-life discussions have been negatively impacted by prognostic uncertainty as well as barriers to in person meetings with families. Summary: The resuscitation of critically ill COVID-19 patients poses new challenges, but the principles remain largely unchanged.